New Semantic Shades of Literary Phraseology: the Black Council by P. Kulish - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article deals with stylistic transformations of a phraseologism of literary origin THE BLACK COUNCIL, which in mass consciousness is connected with: a) the eponymous chronicle novel by P. Kulish; b) a historical event, nominated as Nizhyn General Council of 1663; c) usurpation of power during the Cossacks Age and further economic decline. In modern times, the phraseologism can be considered in other relevant contexts, primarily political ones. To clarify the deactivation of the notion of THE BLACK COUNCIL, the texts of media communication as one of the dominant spheres of the modern society have been used. The study presents data from electronic search engines in which the analyzed phraseologism acts as a time marker. The greatest media reflection on the phraseologism is observed during periods of social shifts: mass actions and revolutions (2004 and 2014), parliamentary crises (2006, 2014 and 2019), presidential campaigns, changing presidents and / or the political course of the country. In fact, the analyzed phraseologism is regarded as a certain ideologeme of the modern Ukrainian political discourse. To verify the author’s ideas, the method of media monitoring was used, which allowed to correctly show the role of the phraseologism and its stylistic transformations in genre syncretism as well as the statistical method, which supported the conclusions made. The author also analyzes broad derivative potential of the investigated phraseologism, which leads to a change in semantics and evolution of Ukrainian literary language as a whole. The author’s attention is drawn to new semantic shades of the analyzed phraseologism, which are related to: a) updating of the language resource in media communication, b) expansion of the world information field, c) adjustment of value guidelines of Ukrainians, d) changing of political situation in the country. In fact, the phraseologism THE BLACK COUNCIL is an effective stylistic resource for describing the political situation, and its semantic transformation enhances media influence on the recipient, given his background knowledge.